The Implementation of Trans-Disciplinary Principle in the Content of Higher School Students Humanitarian Training - Platonova, Raisa I.; Golokova, Vera S.; Ammosova, Liya I.; Barkalova, Nataliya V.; Zorina, Anna V.; Vygodchikova, Natalia N.; Turayev, Rustam R.; Shaidullina, Albina R.; Chernova, Yuliya A. (International Review of Management and Marketing, 2016)
This article is focuses on the scientifically-methodical substantiation of conditions of trans-disciplinary principle realization in the higher school students’ humanitarian training. The article presents the theoretical ideas of trans-disciplinary as a methodology of General cultural norms, values, universals, invariants of the scientific picture of the world, organized form of communication in many disciplines; discloses the potentialities of the implementation of trans-disciplinary principle in the content of higher school students’ humanitarian training; proposes the technology of trans-disciplinary principle implementation; defines the educational software of this process. Materials of the article are intended for the teachers of social-humanitarian disciplines and disciplines of professional cycles, the universities’ Methodists, the organizers of the educational process, attendants of qualification improvement system and teachers’ retraining courses. Keywords: Principle of Trans-Disciplinary, Management of Education, Technology, Students. JEL Classifications: A23, I23, I26